Coping in adolescents: A mediator between stress and disordered eating. (December 2022) - Henderson, Katherine A.; Obeid, Nicole; Buchholz, Annick; Schubert, Nicholas; Flament, Martine F.; Thai, Helen; Goldfield, Gary S.
Abstract: Background: Adolescence is a developmental period that can place individuals at heightened risk of engaging in disordered eating patterns. Stress and coping have been included as etiological factors of eating pathology, yet the mechanism of this relationship in adolescent males and females remains understudied. Aims: This study investigated the role of coping as a mediator in the stress-disordered eating relationship in a sample of adolescents. Demographics/settings: Participants included 2262 grade 7–12 students from a larger cross-sectional study entitled, Research on Eating and Adolescent Lifestyles (REAL). Methodology/analyses: Participants completed measures of perceived stress, life stressors, coping style, and disordered eating. Multiple mediator models of coping were analyzed to examine the extent to which coping mediated the stress-disordered eating relationship, for males and females separately. Findings: Emotion-oriented coping was a significant partial mediator in the relationship between stress (perceived stress, life stressors) and disordered eating in male and female adolescents. Findings suggest adolescents experiencing high stress tend to engage in emotion-oriented coping, which may lead to greater levels of disordered eating. Implications: Interventions targeting effective coping strategies for dealing with different stress types may prevent youth from disordered eating, thus reducing their risk of eating disorders during a vulnerable period in development. Highlights: Stress and coping are important etiological factors of eating pathology in adolescents. Youths' emotional coping mediates relationship between stress and disordered eating. Stressed youth use emotion-oriented coping; may lead to greater disordered eating. Coping strategies for different stress types may prevent disordered eating in youth.